Study the Role of Nasal Scrap Cytology in Allergic Rhinitis Patients in Rural Population - Singhvi, Puneet (Indian J Otolaryngol Head Neck Surg, 2018)
Allergic Rhinitis is one of the gift of modern era. Condition is involving wide range of age group starting from children to old age people. In spite of latest diagnostic facility and advanced treatment, it is still a great challenge for the otorhinolaryngologist. This study was done to perform simple and cost effective test to understand the severity of Allergic Rhinitis. To investigate the patients of allergic rhinitis with specific focus on nasal scrape cytology. After applying inclusion and exclusion criterion were found suitable and hence selected for the present study. 100 patients who were clinically diagnosed on history and examination as allergic rhinitis were included as cases while control group consisted of 100 subjects having no symptoms of allergic rhinitis. These patients were a subjected to nasal scrape cytology for which Cytobrush Plus (Medscand Cell Sampling Kit), Malmo, Sweden, was employed. Mucosal specimens were acquired by scraping the surfaces of the middle thirds of inferior turbinates with Cytobrush Plus (Medscand Cell Sampling Kit), Malmo, Sweden. The samples thus obtained were transferred onto glass slides to be fixed in 95% ethyl alcohol and stained with May Gurwald Gimesa stain to study pattern and profile of different types of cells like eosinophils, goblet cells, mast cells. The nasal eosinophils were studied under 1000 × magnification of light microscope 10-well spread, high power epithelium fields were examined and the quantitative score of nasal eosinophils was rated according to a scale described by Meltzer. In study group all 100 patients underwent nasal scrape cytology. 25 (25%) patients in study group showed grade 1 + nasal eosinophilia followed by grade ½ + in 24 (24%), grade 0 in 22 (22%) and grade 2 + in 21 (21%). In control group 80% of subjects had grade 0 nasal eosinophilia. Difference between nasal eosinophilia in the study and the control group were found to be statistically significant. In study group 54% showed grading > 0.5 + whereas 46% showed ≤ 0.5 + . The sensitivity and specificity were observed to be 54% and 100% respectively. The results thus found were statistically significant. Nasal scrape cytology which was an added dimension proved to be a more specific than sensitive test. The specificity of nasal scrape cytology in our study was 100%. Sensitivity was only 54%. 22% of the patients of allergic rhinitis showed an eosinophil count more than 300/cu mm.